Intervenção baseada em Mindfulness para cuidadores de idosos com demência - Sanchez, Marília Graciela de Almeida Prado (2019)
Introduction: with demographic aging, dementia has become one of the most relevant problems today, whose impacts involve biological, social and psychological factors, both for the affected person and the family caregiver. And this is who, generally, takes responsibility for care in an unprepared manner, contributing to depressive, anxiety and overload. Scientific evidence suggests that Mindfulness-based intervention (MBI) may be a possibility to help these people to improve mental health and consequently the performance of caring activity. Objectives: to analyze the effects of MBI on depressive symptoms, anxious symptoms and burden of family caregivers of elderly people with dementia. Method: it is a randomized controlled trial. The sample (n = 29) was composed by Mindfulness Intervention Group (MIG) (n = 11) and Active Control Group (GCa) (n = 18). All elderly participants were referred from a specialized outpatient clinic of a Federal University in the interior of the state of São Paulo. They were evaluated before and after the intervention (MBI) with duration of eight meetings, during four months, by the Zarit Burden scales and HAD Scale (symptoms of anxiety and depression). In the analysis of the data was used Student's t test for samples and independent and paired. All ethical care was respected during the process of data collection, intervention and analysis. Results: In both groups there was a prevalence of female participants, who lived with the elderly, and with a mean age of 51.6 years for MIG and 56.4 years for MI. No statistically significant differences were identified between the control and intervention groups regarding sociodemographic characteristics. GIM presented improvement in HAD (p = 0.048) whereas for CGa, no significant differences were found in the mean level of the outcome variables. Conclusion: these results highlight the importance of the Mindfulness-based intervention for caregivers of elderly people with dementia to relieve symptoms of anxiety and depression.